Parental leave and maternal labor supply - Astrid Kunze (IZA World of Labor, 2016)
Numerous studies have investigated whether the provision and generosity of parental leave affects the employment and career prospects of women. Parental leave systems typically provide either short unpaid leave mandated by the firm, as in the US, or more generous and universal leave mandated by the government, as in Canada and several European countries. Key economic policy questions include whether, at the macro level, female employment rates have increased due to parental leave policies; and, at the micro level, whether the probability of returning to work and career prospects have increased for mothers after childbirth.
Keywords: J1; J16; J13; 330; labor supply; children; parental leave; skills; return to work; human capital